Technological Solution to Optimize Outpatient Waiting Time for Medical Care Between Multiple Private Healthcare Institutions – A Preliminary Research - Castro-Velásquez, Cesar (2024)
This article proposes a technological solution that allows optimizing the outpatient waiting time for medical care among private health care providers using React Native as a multiplatform tool, since it facilitates the creation of user interfaces efficiently and has one of the most significant numbers of contributors for any repository on GitHub, and the use of Microsoft Azure as a cloud platform due to the fact that it provides the security, privacy and integrity requirements demanded by the Peruvian Ministry of Health (MINSA). This proposal allows users to schedule their medical appointments in a private health institution according to their needs through the following phases: 1) Capture and storage of personal data, 2) Capture of search parameters, and 3) Scheduling of medical appointments. The preliminary case study of the proposal was carried out by collecting a sample of 60 patients, aged between 17 and 65 years of both sexes, who booked medical appointments in an outpatient specialty. The results were compared with the data collected in the SUSALUD user satisfaction survey and with our own survey conducted prior to the solution's implementation. This study effectively optimized medical care waiting time by 54.5%. However, this article contains the preliminary phase of this research. Therefore, it should be considered for future research and address upcoming studies in this critical area.